2005
DOI: 10.1002/eji.200425322
|View full text |Cite
|
Sign up to set email alerts
|

Cross-presentation of phage particle antigen in MHC class II and endoplasmic reticulum marker-positive compartments

Abstract: It has been shown that exogenous antigens can access the MHC class I pathway of professional antigen-processing cells. However, details as to how the MHC class Ipeptide complex forms in the presentation pathway are still poorly understood. Here we used MHC class I-peptide-specific antibodies to investigate the formation and intracellular location of class I-peptide complexes in macrophages. We observed that the formation of class I-peptide complexes occurs within a few hours and lasts for another few hours on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…The mechanisms underlying the efficacy of engineered virions to generate specific and potent antitumor CTLs are currently unknown and are under investigation in our laboratory. It has been previously described by others and by us that filamentous bacteriophage fd are taken up and processed by MHC class I and class II pathways (38,39). This might explain, at least in part, the ability of virions displaying foreign T cell epitopes to elicit potent Th cell-dependent CTL responses.…”
Section: Discussionmentioning
confidence: 75%
“…The mechanisms underlying the efficacy of engineered virions to generate specific and potent antitumor CTLs are currently unknown and are under investigation in our laboratory. It has been previously described by others and by us that filamentous bacteriophage fd are taken up and processed by MHC class I and class II pathways (38,39). This might explain, at least in part, the ability of virions displaying foreign T cell epitopes to elicit potent Th cell-dependent CTL responses.…”
Section: Discussionmentioning
confidence: 75%
“…28,38 CNX may also enhance cross-presentation of exogenous antigens through the class I major histocompatibility complex pathway. 39 MM patients' DCs presenting cancer antigens do not induce an effective T helper or cytotoxic T-lymphocyte response against cancer cells. LV-CNX-modified MM DCs, by contrast, effectively boosted cytokine production in both CD4 and CD8 T cells coupled with increased cancer cell killing activity.…”
Section: Discussionmentioning
confidence: 98%
“…As both soluble antigens and Salmonella are drastically smaller than these beads (endosome volume: ß0.2-1.3 ÎŒm 3 ; Salmonella volume: ß2.0-4.0 ÎŒm 3 ; beads volume: ß14.14 ÎŒm 3 ), it is likely that CO only blocks maturation of small endo/phagosomes. Along these lines, it has been recently shown that particle size determines the composition of the endo/phagosomal membrane in DCs because 3 ÎŒm-beads possess both ER-derived proteins in their membranes (due to ERmediated phagocytosis) and also a remarkable expression of both MHC-I and MHC-II molecules [83][84][85][86][87][88][89][90][91]. This phagosome is known as the ERgosome (Fig.…”
mentioning
confidence: 97%